Flight Test of Attitude Determination System using Multiple GPS Antennae - Jang, Jaegyu; Kee, Changdon (Journal of navigation, 2006)
Small Unmanned Aerial Vehicles (UAVs) or inexpensive airplanes, such as a Cessna single engine aircraft, require a navigation system with a cheap, compact and precise sensor. Over the past ten years, GPS receivers have begun to be used as primary or alternative navigation sensors, because their use can significantly reduce the overall system cost. This paper describes a navigation system incorporating a velocity-based attitude estimation system with an attitude determination system using multiple antennae, which was implemented and tested using a UAV. The main objective was to obtain precise attitude information using low cost GPS OEM boards and antennae. Attitude boundaries are derived from the relationship between the body frame and the wind coordinates, which are used to validate the resolved cycle ambiguity in an Euler angle domain. Angular rate based on Doppler measurements was used to exclude the degenerate pseudo-roll angle information during severe uncoordinated flight. Searching for cycle ambiguity at every epoch of the flight showed that the developed system gave reliable cycle integer solutions, although the carrier phase measurement was subject to additional errors, such as multipath, external interference, and phase centre variation. A flight test was performed using a 1/4-scale Piper J3 Cub model, CMC Allstar OEM boards, OEM AT575-70 antennae, and 700 MHz PC104 board.